PHYSICAL GROWTH AND LUDIC-MOTOR ACTIVITIES (Fiep Bulletin - online, 2013)
On the last decades, obesity has become a world epidemic and involving all ages. Considering that, as soon as the problems of body mass excess are diagnosed and treated, better are the results, this study had as its aim to diagnose the physical growth and the effects of a multi-subject program of the overweight and obesity indexes prevention and reduction on children aged from 7 to 10. This project studied 31 children, among them, 11 were euthrophic and on a overweight risk, 14 overweighted and 6 were obese. The research technique applied was the evaluation of the anthropometric measures (weight and height), using the BMI formula=weight/height2 in order to determine the Body Mass Index (BMI). The results show that the majority of children were overweight, even on the previous and on the post test period. By the analysis of the differences between the values, it could be seen that the program did not have any significant statistical influence (t=0,9373; p>0,05) over the reduction of BMI. It was concluded that the program was not enough to produce changes on the nutritional aspects
Keywords: Overweight; Obesity; Schollars